Adenocarcinoma of the jejunum: management of a rare small bowel neoplasm. Issue 4 (22nd April 2021) - Pereira, Raquel; Tojal, André; Gomes, Aline; Casimiro, Carlos; Moreira, Sara; Vieira, Fortunato; Rodrigues, Pedro
Abstract: Small bowel adenocarcinomas are rare malignant tumors that account for less than 2% of gastrointestinal tumors. Despite a thorough history, physical examination and complete diagnostic workup, the correct diagnosis of small intestinal neoplasm has been established preoperatively in only 50% of cases. Due to the rarity of this disease, there are very few established guidelines for its management and it has been primarily treated the same way as colorectal cancer, even though patient's prognostic outcome is worse. With new guidelines in 2020, we review a clinical case of a 64-year-old male patient with adenocarcinoma of the jejunum treated in our institution.